The Significance of Training for Sustainable Workforce Development in Organizations: A Systematic Literature Review - Chowdhury, Mohammad Imtiaz Uddin (Golden Ratio of Human Resource Management, 2026)
This paper examines the significance of training in fostering sustainable workforce development and enhancing organizational performance. In contemporary organizational contexts, sustainability extends beyond environmental concerns to include the long-term viability of human capital. Training and development play a critical role in reducing employee disengagement, improving work performance, and strengthening organizational competitiveness. This study explores relevant theoretical frameworks, empirical evidence, and organizational practices to demonstrate how training contributes to employee adaptability, engagement, innovation, and alignment with sustainability objectives. Furthermore, the paper highlights the role of continuous learning in building a resilient and future-ready workforce. The findings suggest that sustainability-oriented training programs not only enhance individual competencies but also improve overall organizational effectiveness and brand value. The study concludes by recommending the strategic integration of sustainability-focused training initiatives to support long-term organizational growth and workforce sustainability.